Case Report: A case of epithelioid hemangioendothelioma of the right femoral artery misdiagnosed as arterial occlusion - Shao, Zhengqi; Wang, Jian; Wang, BaiChuan; Hu, HongZhi (Frontiers in Surgery, 2025)
Epithelioid hemangioendothelioma (EHE) is a rare and locally aggressive tumour of vascular endothelial origin, with an estimated prevalence of less than 1 in a million. EHE can arise in any part of the body, most commonly in the liver, lungs, and skeleton, while occurrence in the blood vessels of the extremities is rare. This article reports a rare case of primary epithelioid hemangioendothelioma (EHE) of the right femoral artery. The patient was initially misdiagnosed with lower limb arterial occlusion and treated with stenting and other therapies; however, symptoms recurred, and the diagnosis of EHE was confirmed by pathological biopsy. EHE is very rare and accounts for approximately 1% of all vascular tumours. Based on pathological findings— CD31(+), CD34(−), CAMTA(+)–our patient was diagnosed with WWTR1-CAMTA1 fusion EHE.Treatment of EHE is mainly surgical. In our case, the patient underwent resection of the lesion area and the surrounding soft tissue mass, followed by a reconstruction using a left saphenous vein graft.